Deep roots: Philosophical dimensions of sustainability - Olstad, Tyra A. (Kansas State University, 2009)
Although discussion of "sustainability" necessarily centers on the practical development and application of techniques for "green" living, it is important to consider the philosophical and ethical perspectives that underpin the desire for ecologic and social change. As more and more people seek to find a way to live lightly on and with the earth, they honor a deep legacy of environment-attuned thinkers – individuals from Henry David Thoreau to Gary Snyder, Aldo Leopold to Arne Naess. In presenting a variety of theories and testimonies that explore "why" of sustainability, this talk will (re)inforce commitment to the "what" and "how" of implementation.
Keywords: Green living; Philosophy; Ethics; Social change; Sustainability